P0448CHARACTERISTICS OF PRIMARY GLOMERULAR DISEASE PATIENTS WITH HEMATURIA IN TURKEY: THE DATA FROM TSN-GOLD WORKING GROUP. (6th June 2020) - Sumnu, Abdullah; Turkmen, Kultigin; Cebeci, Egemen; Turkmen, Aydin; Eren, Necmi; Seyahi, Nurhan; Oruc, Aysegul; Dede, Fatih; Derici, Ülver; Basturk, Taner; SAHIN, Garip; Sipahioglu, Murat; et al.
Abstract: Background and Aims: Hematuria is one of the most common laboratory findings in nephrology practice. In different regions of the world, the etiologic causes differ. To date, there is no enough data regarding the clinical and histopathologic characteristics of primary glomerular diseases (PGD) patients with hematuria in our country. Method: Data were obtained from national multicenter (47 centers) data entered into the Turkish Society of Nephrology Glomerular Diseases (TSN-GOLD) database between May 2009 and June 2019. The data of all PGD patients over the age of 16 years who were diagnosed with renal biopsy and had hematuria data were included in the study. The biopsy samples were processed using a light microscopy and immunofluorescence examination. Demographic characteristics such as age, sex, indications for biopsy, primary glomerular diseases, comorbidities, laboratory and biopsy findings of all patients were also recorded. Hematuria was defined as the presence of at least 5 red blood cells/hpf. Results: Data of 3394 patients were included to the study after the exclusion of patients with secondary glomerulonephritis and patients with missing biopsy findings. While 1699 (50.1%) patients had hematuria, 1695 (49.9%) patients did not have hematuria. Demographic, laboratory, and histopathological characteristics of patients with and without hematuria are given in Table. Patients with hematuria had statistically higher systolic blood pressure (SBP), serum blood urea nitrogen, creatinine, albumin, levels and urine pyuria, however, these patients had statistically lower age, body mass index, presence of hypertension and diabetes, eGFR, 24-hour proteinuria, serum total, HDL and LDL-cholesterol and C3 levels when compared with patients without hematuria. Figure depicted the etiologic causes of patients with and without hematuria. According to histopathological findings, number of global sclerotic glomeruli, cellular and fibrocellular crescents, the levels of mesangial proliferation, endocapillary proliferation, exudative changes in glomeruli, severe tubular atrophy, interstitial inflammation, subendothelial deposition, moderate and severe IgA and C3 deposition were found to be significantly higher and the levels of basal membrane thickening, interstitial fibrosis, subepithelial deposition, severe IgG staining were found to be significantly lower in patients with hematuria. Conclusion: This is the first multicenter national report regarding the demographic and histopathologic data of PGD patients with or without hematuria. Hematuria, a feature of nephritic syndrome, was found at a higher than expected in the PGDs presenting with nephrotic syndrome in our national database.